Does Work Stress Mediate the Link Between Job Insecurity, Meaningful Work, and Psychological Well-Being? - Hakim, Arif Rahman; Mora, Linda; Aisha, Dinda; Sulistiarto, Teguh (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2025)
This research explores the impact of job insecurity and meaningful work on psychological well-being, and further investigates whether work stress serves as a mediating factor. The participants in this study were 117 employees. Data collection was conducted using the Indonesian Well-being Scale, Perceived Stress Scale, Job Insecurity Scale, and Work and Meaning Inventory. The research findings indicate that, directly, job insecurity was significantly and negatively linked to psychological well-being. Conversely, meaningful work showed a significant and positive correlation with psychological well-being. Regarding the indirect associations through work stress, neither job insecurity nor meaningful work demonstrated a significant influence on psychological well-being. The findings of this study indicate that organizations need to reduce job insecurity and foster meaningful work as strategies to enhance employees’ psychological well-being. Furthermore, the results highlight that interventions should not only focus on managing work stress but also strengthen intrinsic factors that provide meaning in work.